Zakat: Solusi Pengentasan Kemiskinan dalam Al-Qur’an (Kajian Ketaatan Hamba atas Perintah Rabbnya) - K, M. Yusuf; Abubakar, Achmad; Mahfudz, Muhsin (IQRO: Journal of Islamic Education, 2023)
This article discusses zakat as a solution for alleviating poverty in the Qur'an through the study of servants' obedience to their Lord's commands. The purpose of this article is to provide an overview of the relationship between the solution for poverty alleviation in Islam through zakat, as it is a command from Allah to His believing servants. The research method used is a literature review method or library research. The literature review is specifically aimed at revealing information from scholarly texts derived from books or relevant academic journals related to the topic under discussion. The research findings indicate the importance of the position of zakat in Islam as one of the pillars of Islam with numerous virtues within it. Zakat, in general, can serve as a solution to the issue of poverty, which has been clearly commanded by Allah to His servants. Therefore, the position and function of zakat in Islam must be effectively implemented, not only seen as a command from Allah but also as a solution to the socio-economic problems faced by the community.